2021
DOI: 10.3389/fimmu.2021.721013
|View full text |Cite
|
Sign up to set email alerts
|

Activation Phenotype of Mycobacterium tuberculosis-Specific CD4+ T Cells Promoting the Discrimination Between Active Tuberculosis and Latent Tuberculosis Infection

Abstract: BackgroundRapid and effective discrimination between active tuberculosis (ATB) and latent tuberculosis infection (LTBI) remains a challenge. There is an urgent need for developing practical and affordable approaches targeting this issue.MethodsParticipants with ATB and LTBI were recruited at Tongji Hospital (Qiaokou cohort) and Sino-French New City Hospital (Caidian cohort) based on positive T-SPOT results from June 2020 to January 2021. The expression of activation markers including HLA-DR, CD38, CD69, and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
(84 reference statements)
2
6
0
Order By: Relevance
“…The rationale behind the discriminative power of the other three markers is simple: they are related to the activation and/or enhancement of immune responses, which commonly follow pathogenic infections. Our data gathered on these also confirms what has been published on the topic: CD38 expression on activated CD4 + T-cells was increased in aTB patients after ESAT-6/ CFP-10 stimulation (Luo et al, 2021), but HLA-DR + and Ki-67 + populations showed the most significant association with active disease in all conditions. These findings are consistent with most of the previous research in the field (Adekambi et al, 2015;Silveira-Mattos et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The rationale behind the discriminative power of the other three markers is simple: they are related to the activation and/or enhancement of immune responses, which commonly follow pathogenic infections. Our data gathered on these also confirms what has been published on the topic: CD38 expression on activated CD4 + T-cells was increased in aTB patients after ESAT-6/ CFP-10 stimulation (Luo et al, 2021), but HLA-DR + and Ki-67 + populations showed the most significant association with active disease in all conditions. These findings are consistent with most of the previous research in the field (Adekambi et al, 2015;Silveira-Mattos et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Besides its effect on IGRA results, low PHA response of tuberculosis patients has been shown to qualify as a biomarker for discrimination between latent M. tuberculosis infection and acute tuberculosis [6,7]. Especially a combination of antigen-specific and PHA-induced IFN-γ expression from IGRAs (i.e., antigen/PHA ratios) gained promising results [6][7][8][9][10]. In addition, a recent study indicated potential capacity of antigen/PHA ratios to monitor efficacy of treatment [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several genome-wide transcriptomic studies have been conducted to identify variations in host gene expression profiles in relation to different states of M. tuberculosis infection [ 10–12 ]. However, while most studies have primarily focused on discerning differences between patients with active TB and individuals with LTBI [ 10 , 13 ], little is known about the diverse host responses among household contacts (HHCs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several genome-wide transcriptomic studies have been conducted to identify variations in host gene expression profiles in relation to different states of M. tuberculosis infection [ 10–12 ]. However, while most studies have primarily focused on discerning differences between patients with active TB and individuals with LTBI [ 10 , 13 ], little is known about the diverse host responses among household contacts (HHCs). Thus, the objective of this study was to conduct a prospective investigation in mainland China, aiming to evaluate transcriptome signatures in human peripheral blood mononuclear cells (PBMCs) of HHCs with distinct clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%